2022
DOI: 10.3390/ijms232113044
|View full text |Cite
|
Sign up to set email alerts
|

High Glycemia and Soluble Epoxide Hydrolase in Females: Differential Multiomics in Murine Brain Microvasculature

Abstract: The effect of a high glycemic diet (HGD) on brain microvasculature is a crucial, yet understudied research topic, especially in females. This study aimed to determine the transcriptomic changes in female brain hippocampal microvasculature induced by a HGD and characterize the response to a soluble epoxide hydrolase inhibitor (sEHI) as a mechanism for increased epoxyeicosatrienoic acids (EETs) levels shown to be protective in prior models of brain injury. We fed mice a HGD or a low glycemic diet (LGD), with/wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…The t-AUCB was provided in the drinking water using polyethylene glycol 400 (PEG400) (Millipore, Burlington, MA, USA) as a vehicle from 20 weeks of age until sacrifice at 32 weeks of age (Figure 1B). We chose this timeline of treatment and sacrifice to align with our previous publications regarding sEHI, which found this length of treatment sufficient to induce changes in the brain microvascular transcriptome [54,56,57]. Consistent with prior protocols, the final contents of the drinking water were 1% (by volume) PEG400 and 10 mg/L t-AUCB [58,59].…”
Section: Soluble Epoxide Hydrolase Inhibitor (Sehi)mentioning
confidence: 94%
“…The t-AUCB was provided in the drinking water using polyethylene glycol 400 (PEG400) (Millipore, Burlington, MA, USA) as a vehicle from 20 weeks of age until sacrifice at 32 weeks of age (Figure 1B). We chose this timeline of treatment and sacrifice to align with our previous publications regarding sEHI, which found this length of treatment sufficient to induce changes in the brain microvascular transcriptome [54,56,57]. Consistent with prior protocols, the final contents of the drinking water were 1% (by volume) PEG400 and 10 mg/L t-AUCB [58,59].…”
Section: Soluble Epoxide Hydrolase Inhibitor (Sehi)mentioning
confidence: 94%
“…To date, the work of the Basic Science and Animal Modeling core has demonstrated that both hyperlipidemic and hyperglycemic stress induces sex-specific expression of protein coding and non-coding genes [85][86][87][88][89][90]. Interestingly, the functional cellular pathways are primarily associated with neurodegeneration in male [89], and neuroprotection in female mice [88].…”
Section: Consultation and Collaborationmentioning
confidence: 99%